Global burden, trends and projections analysis of interstitial lung disease and pulmonary sarcoidosis in elderly adults (aged 55+ Years) based on GBD 2021 - Zhilan Huang; Tingyi Xie; Mingwen Tang; Zhuni Chen; Dan Jia; Anqi Su; Zhujin Jin; Tuliang Liang; Wei Xie (PLoS ONE, 2026)
Background Pulmonary fibrosis is a severe chronic lung disease whose prevalence has been rising in recent years, representing one of the major respiratory health challenges globally in the 21st century. The burden of this disease on the elderly population is garnering growing attention, particularly as the global population ages. The Global Burden of Disease (GBD) study has provided valuable insights; however, systematic analyses focused on this condition remain limited. To date, few studies have specifically examined interstitial lung disease and pulmonary sarcoidosis among individuals aged 55 years and older. This study aims to conduct a comprehensive analysis of burden trends from 1990 to 2021 for those aged 55 and above and to project future trends up to 2035. Methods Our approach utilizes the estimation of four broad component measures: incidence, prevalence, death and Disability-Adjusted Life Years (DALYs), using data on ILD&PS from the Global Burden of Disease (GBD) 2021 database. Joinpoint regression models were applied to calculate the average annual percentage change (AAPC) in order to analyze temporal trends in disease burden and to identify years with significant trend shifts. Analyses were further stratified by age, sex, region, country, and Sociodemographic Index (SDI). Additionally, a Bayesian age-period-cohort (BAPC) model was used to project future disease burden trends. Results Between 1990 and 2021, significant increases were observed in incidence, DALYs, and death rates for ILD&PS (AAPC incidence = 1.09, 95% CI: 1.04 to 1.15; AAPC DALYs = 1.10, 95% CI: 0.97 to 1.23; AAPC death = 1.65, 95% CI: 1.47 to 1.83). In 2021, the total number of incident cases reached 284,887 (95% UI 248,300–328,800), with the highest incidence rates observed in Andean Latin America. Across age- and sex-specific analyses, global burden trends were similar, though males consistently exhibited higher rates than females. The oldest age group (95 + years) had the highest incidence and DALYs rates among all age strata. Furthermore, incidence rates increased most markedly in high-SDI regions, showing a strong positive correlation between SDI and incidence. Bayesian age–period–cohort (BAPC) analyses indicated that while prevalence rates are projected to decline slightly, incidence rates are expected to continue rising. Both males and females showed a dip then rise in prevalence trends, but the increase was more pronounced among females. In 2035, the highest number of incident cases is projected to occur in the 65–69 age group, whereas the highest incidence rate is predicted in the 95 + age group. Conclusions A concerning upward trend in incidence, DALYs, and deaths related to ILD&PS was observed in the global population aged 55 years and older, particularly among females. To our knowledge, this is the first study to comprehensively analyze the burden of ILD&PS in this age group from 1990 to 2021. Our findings on epidemiological trends and their variations across geography, SDI, age, and sex can inform policy-makers in designing targeted strategies to mitigate the anticipated rise in disease burden.